2006
DOI: 10.1074/jbc.m606045200
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated Kinase Inhibits the Epithelial Na+ Channel through Functional Regulation of the Ubiquitin Ligase Nedd4-2

Abstract: We recently found that the metabolic sensor AMP-activated kinase (AMPK) inhibits the epithelial Na ؉ channel (ENaC) through decreased plasma membrane ENaC expression, an effect requiring the presence of a binding motif in the cytoplasmic tail of the ␤-ENaC subunit for the ubiquitin ligase Nedd4-2. To further examine the role of Nedd4-2 in the regulation of ENaC by AMPK, we studied the effects of AMPK activation on ENaC currents in Xenopus oocytes co-expressing ENaC and wild-type (WT) or mutant forms of Nedd4-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
158
3
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(172 citation statements)
references
References 65 publications
5
158
3
6
Order By: Relevance
“…However, it is not yet clear what the potential upstream regulators of the IKK pathway are in this case. Interestingly, the metabolic sensor AMPK has been reported to be an upstream inhibitor of IKK in several cell systems (37)(38)(39), and we have shown that AMPK inhibits ENaC, also via effects on Nedd4-2 in an AMPK phosphorylation-dependent manner (7,20). Further studies to test for the potential involvement of AMPK and other cellular signaling pathways as upstream regulators of the IKK␤-dependent regulation of ENaC are thus warranted.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is not yet clear what the potential upstream regulators of the IKK pathway are in this case. Interestingly, the metabolic sensor AMPK has been reported to be an upstream inhibitor of IKK in several cell systems (37)(38)(39), and we have shown that AMPK inhibits ENaC, also via effects on Nedd4-2 in an AMPK phosphorylation-dependent manner (7,20). Further studies to test for the potential involvement of AMPK and other cellular signaling pathways as upstream regulators of the IKK␤-dependent regulation of ENaC are thus warranted.…”
Section: Discussionmentioning
confidence: 99%
“…As the E3 ubiquitinprotein ligase Nedd4-2 has emerged as a central locus for the regulation of ENaC expression at the apical plasma membrane (21), we considered that ENaC regulation by IKK␤ may be mediated indirectly through Nedd4-2. Of note, Nedd4-2 has been recently reported to be a substrate for various kinases, including SGK1, PKA, AMPK, and Grk2, which may modulate Nedd4-2 function (3,4,20,22). To test whether IKK␤ phosphorylates Nedd4-2 in vitro, FLAG-xNedd4-2 was expressed in and immunoprecipitated from HEK-293 cell lysates, and in vitro phosphorylation assays were performed (Fig.…”
Section: Endogenous Regulation Of Enac By Ikk␤ In Mpkccd C14mentioning
confidence: 99%
See 3 more Smart Citations